Can mind-wandering be timeless? Atemporal focus and aging in mind-wandering paradigms - Jackson, Jonathan D.; Weinstein, Yana; Balota, David A. (Frontiers in Psychology, 2013)
Recent research has examined how often mind-wandering occurs about past versus future events. However, mind-wandering may also be atemporal, although previous investigations of this possibility have not yielded consistent results. Indeed, it is unclear what proportion of mind-wandering is atemporal, and also how an atemporal response option would affect the future oriented bias often reported during low-demand tasks used to measure mind-wandering. The present study examined self-reported (Experiment 1) and probe-caught (Experiment 2) mind-wandering using the low-demand Sustained Attention to Response Task (SART) in younger (18-30) and older (50-73) adults in an experimental paradigm developed to measure mind-wandering in a sample using Amazon’s Mechanical Turk. Across self-reported and probe-caught mind-wandering, the atemporal response option was used at least as frequently as past or future mind-wandering options. Although older adults reported far fewer mind-wandering events, they showed a very similar temporal pattern to younger adults. Most importantly, inclusion of the atemporal report option affected performance on the SART and selectively eliminated the prospective bias in self-reported mind-wandering, but not in probe-caught mind-wandering. These results suggest that both young and older participants are often not thinking of past or future events when mind-wandering, but are thinking of events that cannot easily be categorized as either.